Rapid evolution of SARS-CoV-2 in domestic cats. Issue 2 (30th September 2022) - Bashor, Laura; Gagne, Roderick B; Bosco-Lauth, Angela; Stenglein, Mark; VandeWoude, Sue
Abstract: SARS-CoV-2 (SARS2) infection of a novel permissive host species can result in rapid viral evolution. Data suggest that felids are highly susceptible to SARS2 infection, and species-specific adaptation following human-to-felid transmission may occur. We employed experimental infection and analysis of publicly available SARS2 sequences to observe variant emergence and selection in domestic cats. Three cohorts of cats ( N  = 23) were inoculated with SARS-CoV-2 USA-WA1/2020 or infected via cat-to-cat contact transmission. Full viral genomes were recovered from RNA obtained from nasal washes 1–3 days post-infection and analyzed for within-host viral variants. We detected 118 unique variants at ≥3 per cent allele frequency in two technical replicates. Seventy of these (59 per cent) were nonsynonymous single nucleotide variants (SNVs); the remainder were synonymous SNVs or structural variants. On average, we observed twelve variants per cat, nearly 10-fold higher than what is commonly reported in human patients. We observed signatures of positive selection in the spike protein and the emergence of eleven within-host variants located at the same genomic positions as mutations in SARS2 variant lineages that have emerged during the pandemic. Fewer variants were noted in cats infected from contact with other cats and in cats exposed to lower doses of cultured inoculum. An analysis of ninety-three publicly available SARS2 consensus genomes recovered from naturally infected domestic cats reflected variant lineages circulating in the local human population at the time of sampling, illustrating that cats are susceptible to SARS2 variants that have emerged in humans, and suggesting human-to-felid transmission occurring in domestic settings is typically unidirectional. These experimental results underscore the rapidity of SARS2 adaptation in felid hosts, representing a theoretical potential origin for variant lineages in human populations. Further, cats should be considered susceptible hosts capable of shedding virus during infections occurring within households.